STRATEGI PENGEMBANGAN MARKETING BANK BTPN SYARIAH CABANG TUBAN - Saputri, Zulinda Kurniawati; Ansori, Miswan (LPPM Universitas Bina Bangsa, 2025)
BTPN Syariah still faces many shortcomings and obstacles. Among the external challenges is the increasing number of banks, both Islamic and conventional. As for internal issues or challenges, BTPN Syariah has a limited number of experts in this field, whether in marketing or other areas. Most of the employees at BTPN Syariah are high school graduates or equivalent. The purpose of this study is to explore the Development Strategy of BTPN Syariah Bank. A qualitative approach and descriptive research type were used in this study. The data required by the researcher comes from primary and secondary data sources. In this research, the techniques used to obtain data include observation, interviews, and documentation. The techniques used to analyze the data consist of data reduction, data presentation, and drawing conclusions. The research found that the Tuban branch of BTPN Syariah employs strategies such as tailoring funding and financing products to meet community needs, using face-to-face promotional strategies and collaboration with institutions, and improving access by offering proactive services